2022
DOI: 10.22219/mb.v12i01.19218
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Technology on the Financial Satisfaction of MSMEs in Malang

Abstract: This study aims to determine the effect of financial technology on financial satisfaction of Small Businesses (SMEs) in Malang City. By using primary data and random sampling, as well as using a questionnaire distributed to entrepreneurs and measured with a Likert scale. The collection of data on MSME respondents in the city of Malang is based on the distribution of questionnaires. The research objectives are as follows: To know the influence of Fintech on financial satisfaction?”. The analytical method used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Menurut Rahadjeng et al, (2021) financial technology merupakan bentuk kombinasi diantara layanan keuangan dan teknologi yang kemudian dapat mengubah cara tradisional berbisnis menjadi model bisnis yang sederhana dimana sebelumnya pembayaran harus dilakukan secara langsung dan disediakan tunai, tetapi sekarang dimungkinkan untuk bernegosiasi dari jarak jauh dalam hitungan detik. Teknologi bisnis adalah penggunaan teknologi dalam manajemen bisnis.…”
Section: Financial Technologyunclassified
“…Menurut Rahadjeng et al, (2021) financial technology merupakan bentuk kombinasi diantara layanan keuangan dan teknologi yang kemudian dapat mengubah cara tradisional berbisnis menjadi model bisnis yang sederhana dimana sebelumnya pembayaran harus dilakukan secara langsung dan disediakan tunai, tetapi sekarang dimungkinkan untuk bernegosiasi dari jarak jauh dalam hitungan detik. Teknologi bisnis adalah penggunaan teknologi dalam manajemen bisnis.…”
Section: Financial Technologyunclassified
“…Menurut (Ruhmi & Tanjung, A.A., 2023) : menunjukkan bahwa peran payment gateway berpengaruh signifikan terhadap kinerja keungan pada UMKM. Menurut (Retno Rahadjeng et al, 2021) menunjukkan bahwa peran payment gateway berpengaruh terhadap kinerja keuangan pada UMKM.…”
Section: Pendahuluanunclassified

Peran Pembayaran Digital Payment Gateway Dalam Meningkatkan Kinerja Keuangan Pada UMKM

Angelia Alfatwa Rusandi Siregar,
Heny Triastuti Kurnia Ningsih,
Pretty Nur A’yuni Laoli
2023
CiDEA Journal
“…Perwitasari, (2022) found that MSMEs were generally willing to embrace fintech for reasons including perceived utility and perceived ease of use in helping to accelerate the delivery of services to consumers through fintech. Use of MSME financial technologies such as peer-to-peer lending, risk and investment management, market aggregators and payment gateways, in order to manage MSME financial performance (Rahadjeng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%